Reduced Membrane Insertion of CLC-K by V33L Barttin Results in Loss of Hearing, but Leaves Kidney Function Intact - Tan, Hua; Bungert-Plümke, Stefanie; Fahlke, Christoph; Stölting, Gabriel (Frontiers in Physiology, 2017)
In the mammalian ear, transduction of sound stimuli is initiated by K+ entry through mechano-sensitive channels into inner hair cells. K+ entry is driven by a positive endocochlear potential that is maintained by the marginal cell layer of the stria vascularis. This process requires basolateral K+ import by NKCC1 Na+-2Cl–K+ co-transporters as well as Cl- efflux through ClC-Ka/barttin or ClC-Kb/barttin channels. Multiple mutations in the gene encoding the obligatory CLC-K subunit barttin, BSND, have been identified in patients with Bartter syndrome type IV. These mutations reduce the endocochlear potential and cause deafness. As CLC-K/barttin channels are also expressed in the kidney, patients with Bartter syndrome IV typically also suffer from salt-wasting hyperuria and electrolyte imbalances. However, there was a single report on a BSND mutation that resulted only in deafness, but not kidney disease. We herein studied the functional consequences of another recently discovered BSND mutation that predicts exchange of valine at position 33 by leucine. We combined whole-cell patch clamp, confocal microscopy and protein biochemistry to analyze how V33L affects distinct functions of barttin. We found that V33L reduced membrane insertion of CLC-K/barttin complexes without modifying unitary CLC-K channel function. Our findings support the hypothesis of a common pathophysiology for the selective loss of hearing due to an attenuation of the total chloride conductance in the stria vascularis while providing enough residual function to maintain normal kidney function.